NOVEL MUTATIONS IN PAX9 GENE ASSOCIATED WITH DENTAL ANOMALIES- A REVIEW - J, Kiren.; Priyadharsini.J, Vijayashree; Sivaswamy, Vinay (International Journal of Psychosocial Rehabilitation, 2020)
Dental anomalies such as tooth agenesis are caused by disturbances and gene mutations that occur during odontogenesis. Human genetic variations have long been of researchers’ interest, as they are partly responsible for the inter-individual response to drugs, infections, and several other phenotypes related to the development and progression of the disease. Tooth development is an intricate process that involves a complex interplay of genes acting in symphony to exhibit the trait. Mutations or genetic errors in the DNA sequences encoding proteins involved in the process of odontogenesis have been identified in recent years. Some of the genes of prime importance are the homeobox genes, which are known to play an important role in tooth development. Several genes, such as PAX, MSX, AXIN, and DLX, have been implicated in the process of odontogenesis. Animal models used in earlier studies reported that PAX9-deficient knockout mice exhibit missing molars due to an arrest of tooth development at the bud stage. The aim of this review was to prepare an exhaustive collection of PAX9 mutation panels reported to be associated with dental anomalies. The literature review will also provide a comprehensive understanding of variations observed in the PAX9 gene in association with several common dental anomalies.